Laser capture microdissection enables transcriptomic analysis of dividing and quiescent liver stages of Plasmodium relapsing species. (13th March 2017) - Cubi, Roger; Vembar, Shruthi S.; Biton, Anne; Franetich, Jean‐Francois; Bordessoulles, Mallaury; Sossau, Daniel; Zanghi, Gigliola; Bosson‐Vanga, Henriette; Benard, Magalie; Moreno, Alicia; Dereuddre‐Bosquet, Nathalie; Le Grand, Roger; et al.
Summary: Dormant liver stage forms (hypnozoites) of the malaria parasite Plasmodium vivax present major hurdles to control and eradicate infection. Despite major research efforts, the molecular composition of hypnozoites remains ill defined. Here, we applied a combination of state‐of‐the‐art technologies to generate the first transcriptome of hypnozoites. We developed a robust laser dissection microscopy protocol to isolate individual Plasmodium cynomolgi hypnozoites and schizonts from infected monkey hepatocytes and optimized RNA‐seq analysis to obtain the first transcriptomes of these stages. Comparative transcriptomic analysis identified 120 transcripts as being differentially expressed in the hypnozoite stage relative to the dividing liver schizont, with 69 and 51 mRNAs being up‐ or down‐regulated, respectively, in the hypnozoites. This lead to the identification of potential markers of commitment to and maintenance of the dormant state of the hypnozoite including three transcriptional regulators of the ApiAP2 family, one of which is unique to P. cynomolgi and P. vivax, and the global translational repressor, eIF2a kinase eIK2, all of which are upregulated in the hypnozoite. Together, this work not only provides a primary experimentally‐derived list of molecular markers of hypnozoites but also identifies transcriptional and posttranscriptional regulation of gene expression as potentially being key to establishing and maintaining quiescence. Abstract : Quiescent liver stage forms of the malaria parasite Plasmodium vivax, which lead to a majority of malaria relapses, have thus far been refractory to molecular characterization. To overcome this, we developed a coupled immunostaining‐laser capture microdissection approach and performed transcriptomics (using RNA‐seq) of dividing and quiescent liver parasites ( P. cynomolgi ). Differential expression analysis identified potential, unique biomarkers of the quiescent state, which could aid both phenotypic characterization and drug design.